Enhancing AES Key Generation Using Diffie-Hellman Method for Image Security - Sinambela, Rifdahtul Ghinaa; Achmad Fauzi; Husnul Khair (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
The increasing need for secure image transmission has led to the development of cryptographic techniques that combine encryption algorithms and secure key exchange methods. This paper proposes a system for enhancing the security of digital images by using the Advanced Encryption Standard (AES) combined with the Diffie-Hellman method for key generation. AES is applied for encryption and decryption, while Diffie-Hellman ensures the secure exchange and generation of secret keys. The system, developed in Microsoft Visual Basic .NET 2010, was tested on various image formats and demonstrated effective protection against brute force attacks. This approach ensures secure digital image transmission and confidentiality.